2005
DOI: 10.1677/joe.1.05837
|View full text |Cite
|
Sign up to set email alerts
|

Ghrelin regulates proliferation and differentiation of osteoblastic cells

Abstract: It has previously been reported that growth hormone secretagogues (GHS) may have a role in the regulation of bone metabolism in animals and humans. In this study we evaluated the effect of ghrelin, the endogenous ligand of GHS receptors, on the proliferation rate and on osteoblast activity in primary cultures of rat calvaria osteoblasts. In the same experiments, we compared the effects of ghrelin with those of hexarelin (HEXA) and EP-40737, two synthetic GHS with different characteristics. Both ghrelin and HEX… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
121
5
4

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(142 citation statements)
references
References 37 publications
12
121
5
4
Order By: Relevance
“…Adiponectin, which increases osteoblast proliferation and differentiation (Oshima et al 2005) but has controversial effect on bone mass in vivo (Williams et al 2009), can stimulate AMPK phosphorylation in MC3T3-E1 osteoblastic cells (Kanazawa et al 2007). We showed that AMPK phosphorylation and activity in ROS17/2.8 cells was stimulated by ghrelin (Shah et al 2010), a hormone known to stimulate osteoblast differentiation and function (Maccarinelli et al 2005, van der Velde et al 2008. Dexamethasone, a synthetic glucocorticoid that has been shown to induce osteoblastic differentiation and bone formation in several culture systems (Delany et al 1994), stimulates AMPK phosphorylation in primary osteoblasts (unpublished results, M Shah, J Jeyabalan, B Viollet & C Chenu).…”
Section: Subunit Expression and Ampk Regulation In Bone Cellsmentioning
confidence: 70%
See 1 more Smart Citation
“…Adiponectin, which increases osteoblast proliferation and differentiation (Oshima et al 2005) but has controversial effect on bone mass in vivo (Williams et al 2009), can stimulate AMPK phosphorylation in MC3T3-E1 osteoblastic cells (Kanazawa et al 2007). We showed that AMPK phosphorylation and activity in ROS17/2.8 cells was stimulated by ghrelin (Shah et al 2010), a hormone known to stimulate osteoblast differentiation and function (Maccarinelli et al 2005, van der Velde et al 2008. Dexamethasone, a synthetic glucocorticoid that has been shown to induce osteoblastic differentiation and bone formation in several culture systems (Delany et al 1994), stimulates AMPK phosphorylation in primary osteoblasts (unpublished results, M Shah, J Jeyabalan, B Viollet & C Chenu).…”
Section: Subunit Expression and Ampk Regulation In Bone Cellsmentioning
confidence: 70%
“…The bone loss in age-related osteoporosis is associated with more adipogenesis and less bone formation (Pei & Tontonoz 2004). Second, there are direct actions on bone of hormones produced by adipocytes, such as adiponectin and leptin, as well as of hormones released by the pancreas, gut and pituitary (Cornish et al 1996, Maccarinelli et al 2005, Williams et al 2009). In addition, the recent discovery that leptin can inhibit bone formation through hypothalamic and sympathetic nervous system relays , Takeda et al 2002, Elefteriou et al 2005 has demonstrated that bone can not only be directly affected by hormones which have receptors on bone cells, but can also be influenced by the same hormones acting on receptors in the central nervous system (CNS).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported a significant stimulation of osteoblast proliferation and an increased ALP activity in osteoblasts in response to ghrelin (7,17,18). Ghrelin stimulates growth hormone secretion both in vivo and in vitro, and may therefore have a positive effect on bone.…”
Section: Discussionmentioning
confidence: 95%
“…Ghrelin stimulates the proliferation and inhibits apoptosis of the H9c2 cardiomyocyte cell line [4], human adrenal zona glomerulosa cells [101], preadipocytes [76], osteoblastic cells [96] and pancreatic beta-cells [59] and rat fetal spinal cord [126] and skin cells [108]. Thus, peripheral actions of ghrelin result not only from modulation of function, but also from regulation of survival/proliferation of target cells.…”
Section: Cellular Proliferationmentioning
confidence: 99%